Prevention Behavior of Related to COVID-19 Among Food Handlers in Restaurants in Pontianak City, Indonesia - Linda Suwarni; Selviana Selviana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The spreading of COVID-19 has been a disadvantage to all countries around the world. The COVID-19 situation in Indonesia based on the date April 26th, 2021 showed that 44,500 people have died, 1,636,194 cases infected, and 1,492,322 positive cases were declared cured. The COVID-19 can be transmitted through food handlers if they do not comply with health protocols. Perceptions about COVID-19 affect food handler compliance with health protocols. This study aimed to examine the correlation between the perception of food handlers in restaurants and the prevention behavior of COVID-19. Methods: This study adopted a cross-sectional design and was conducted between July-August 2020 in 90 food handlers in restaurants in Pontianak City, and data were collected through random sampling. The univariate and bivariate (Chi-Square) were used to analyze the data. Ethical approval was obtained from Faculty of Public Health, Universitas Muhammadiyah Semarang (Certificate of approval No. 373/KEPK-FKM/UNIMUS/2020). Results: This study found only three independent variables have significance with prevention behavior of spreading of COVID-19 such as physical activity (p-value 0.011), seeking or getting COVID-19 information (p-value 0.036), and perception of self-efficacy (p-value 0.005). Additionally, the rest of the independent variables have no significance related to prevention behavior of spreading of COVID-19 like sex, education level, economic effect, smoke status, perceived vulnerability, and perception of the hoax information spread. Conclusion: The strongest independent variable is a perception of self-efficacy which means that the food handlers who had a poor perception of self-efficacy tend to do not practice the prevention behavior of COVID-19. The Future studies should address stakeholder role to educate and train the food handlers to increase their self-efficacy in terms of health problems, including COVID-19.